The interactive effects of climate, land cover change and damming on the flow regime and fine sediment dynamics of a tropical river - Lum, Zoe Xin Yi (2023)
Tropical river ecosystems are being increasingly modified by the accelerated construction of hydropower dams. Dams are known to have detrimental effects on downstream flows and sediment transport, with long-lasting implications for fluvial processes, habitats and ecosystems. The tropics are also experiencing high rates of deforestation and forest degradation. These types of land use change can alter components of the hydrological cycle through the modification of terrain characteristics, evapotranspiration and fine sediment runoff. Moreover, predictions of increased temperatures and changes in precipitation in tropical regions may further modify the hydrological cycle and, in turn, river flows.